Three point bending flexural strength of cement treated tropical marine soil reinforced by lime treated natural fiber - Anggraini V.; Asadi A.; Syamsir A.; Huat B.B.K. (Elsevier B.V., 2023)
Bending tests; Cements; Chemical analysis; Elastic moduli; Fibers; Lime; Mixtures; Pavements; Reinforcement; Road construction; Roads and streets; Soil cement; Soil testing; Soils; Strength of materials; Tropics; Cement treated clay; Coconut fiber; Flexural behavior; Load deflection; Marine clays; Three point bending; Bending strength